A medium-range language to describe different VET systems - Höhns, Gabriela [Verfasser] (My University, 2019)
"This paper proposes the British educational sociologist Basil Bernstein's theoretical concepts to develop medium-range languages of description for different VET systems. The conceptual tools used are 'classification' and 'framing' along with their 'recognition rules'. The central categories for analysis are the classificatory relations at the macro-social level, the 'pedagogic discourse' regulating space-time-discourse relations and projecting transmitters and acquirers, and the 'pedagogic practice' ('framing') at the micro-level of transmission. A research example shows macro-micro relations in Germany's dual system of VET according to these categories and with the conceptual instrument of 'framing'. The systematic and rule-related development of a medium-range 'second language of description' allows one to relate the concepts to different empirical contexts (such as schools and training companies) in a noncircular way. The discussion suggests the use of Bernstein's concepts for extending the current research to differently organised forms of vocational education, from school-based through regulated company transmission - as in Germany's dual system - to unregulated company transmission." (author's abtract; BIBB-Doku)
Keywords: S 4.3 Steuerung; Berufsbildungssystem; Bildungssteuerung; Berufsausbildung; Bernstein, Basil; Linguistik